(untitled) (PEGADA - A Revista da Geografia do Trabalho, 2014)
Introduction: The São Francisco River Basin Committee (CBHSF) was set up by presidential decree in 2001 with the aim of achieving decentralized and participatory management of its water. The São Francisco River flows overland for 2700 km from its source in the Serra da Canastra (MG) to its mouth between Sergipe (SE) and Alagoas (AL). The river passes through the states of Bahia (BA), Pernambuco (PE), Goiás (GO) and the Federal District (DF). Central to the discussion in this research on the transposition of the São Francisco River is question of conflict concerning water management in the São Francisco River Basin Committee, making a nonsense of its power to function, contrary to the project, and the Federal Government which initiated the work and approved the budget. Hence, this study aims to analyze water management in the São Francisco river basin from the initiation of the CBHSF in order to understand how approval of the project and implementation of the work ran against the statutory representation of the committee. Methodology and Development: Having a qualitative approach, the study will be divided between theoretical research based on authors who study the topic of water and its transformation into a water resource and the major landowners of the north-east semi-arid zone in the context of transposition; the dynamics and politics of the river basin; as well as the role of the river basin committees in the process of decentralizing Brazilian water management, specifically concerning the São Francisco River and its state and interstate committees. Documentary research will take into account National Water Resources Law 9.433/1997; state water policies; documentary archives of the river basin committees (state and interstate), as well as the agencies participating in the integration project, such as the National Water Agency (ANA), the Integration Ministry (MI), and the Environment Ministry (MMA). Further data will be obtained using the transcripts of semi-structured interviews with presidents of the river basin committees as well as visiting transposition works and attending CBHSF meetings. Final thoughts: The transposition of the São Francisco River demonstrates how the legacy of Brazilian governmental centralization policies holds back the participatory process of the river basin committees, encroaching on their legal and institutional positions as regards water in the north-east semi-arid zone amid the persistence of drought.